Pengaruh Komunikasi, Fasilitas Belajar, Dan Lingkungan Terhadap Prestasi Belajar Matematika Bilingual Bagi Siswa Kelas X SMA Negeri 1 Sukoharjo - Astuti, Ria Rustikaningrum Murti, Prof. Dr. Budi Murtiyasa M. Kom (2013)
The aim of this study is to study and to find out empirical envidences of the communication, learning facilities,and environment to the bilingual class student learning achievement on mathematics subjects in SMA Negeri 1 Sukoharjo. The type of study is used correlation descriptive study. Descriptive study is done to gain an accurate descrition and picture about some facts related to the variables used is the study. Correlation is done to see the influence among the dependent and independent variables used in this study through hypothesis examination. The research methods used in this study are survey and documentation, where the survey is done to the grade bilingual student of 2012/2013 school year, in SMA negeri 1 Sukoharjo by using questionnaire to get the research data, which then it is processed to get a result, whether the communication, learning facilities, and environment variables give influence to the bilingual class student learning achievement on mathematics subject in SMA Negeri 1 Sukoharjo. The sample of this research is 60 student. The result of this study, has been founded that simultaneously, the communication, learning facilities, and environment variables give positive and significant influence to the learning achievement of the bilingual class on mathematics subject. Partially, the communication, learning facilities, and environment variables also give positive and significant influence to learning achievement of the bilingual class on mathematics subjects.